Water Resources for Algae‐Based Biofuels. (August 2013) - Rastegary, Jalal; Shirazi, Saeid Aghahossein; Fernandez, Tracy; Ghassemi, Abbas
Abstract Adequate energy and available water resources are two of the major requirements for sustaining human progress, yet modern society faces volatile energy availability, prices, and environmental concerns, as well as shortages of drinking water in many parts of the world. Alternative energy produced from biomass such as algae has great potential to utilize sources of water not suitable for consumption. A factorial experiment with CRD (Complete Randomized Design) arrangement was conducted using three growth media: geothermal water, Bold's Basal Medium (BBM), and combination of 50 percent BBM + 50 percent geothermal water. The experiments were conducted utilizing three combinations of illumination periods (12:12, 16:8, and 24:0) to grow the algae Chlorella sorokiniana (UTEX 1230). The results indicated significant differences in biomass production rates. Statistical analysis showed that 50 percent BBM + 50 percent geothermal water with 16:8 light cycle maximized biomass production. The pH in BBM increased from 7 to 10.37 and was significantly higher than both geothermal water (9.06) and 50 percent BBM + 50 percent geothermal water (9.21).